The experience of blood glucose monitoring in people with type 2 diabetes mellitus (T2DM). Issue 2 (17th December 2021) - Stedman, Mike; Rea, Rustam; Duff, Christopher J.; Livingston, Mark; McLoughlin, Katie; Wong, Louise; Brown, Stephen; Grady, Katherine; Gadsby, Roger; Gibson, John M.; Paisley, Angela; Fryer, Anthony A.; et al.
Abstract: Background: Finger prick blood glucose (BG) monitoring remains a mainstay of management in people with type 2 diabetes (T2DM) who take sulphonylurea (SU) drugs or insulin. We recently examined patient experience of BG monitoring in people with type 1 diabetes (T1DM). There has not been any recent comprehensive assessment of the performance of BG monitoring strips or the patient experience of BG strips in people with T2DM in the UK. Methods: An online self‐reported questionnaire containing 44 questions, prepared following consultation with clinicians and patients, was circulated to people with T2DM. 186 responders provided completed responses (25.5% return rate). Fixed responses were coded numerically (eg not confident = 0 fairly confident = 1). Results: Of responders, 84% were treated with insulin in addition to other agents. 75% reported having had an HbA1c check in the previous 6 months. For those with reported HbA1c ≥ 65 mmol/mol, a majority of people (70%) were concerned or really concerned about the shorter term consequences of running a high HbA1c This contrasted with those who did not know their recent HbA1c, of whom only 33% were concerned/really concerned and those with HbA1c <65 mmol/mol of whom 35% were concerned. Regarding BG monitoring/insulin adjustment, only 25% of responders reported having sufficient information with 13% believing that the accuracy and precision of their BG metre was being independently checked. Only 9% recalled discussing BG metre accuracy when their latest metre was provided and only 7% were aware of the International Standardisation Organisation (ISO) standards for BG metres. 77% did not recall discussing BG metre performance with a healthcare professional. Conclusion: The group surveyed comprised engaged people with T2DM but even within this group there was significant variation in (a) awareness of shorter term risks, (b) confidence in their ability to implement appropriate insulin dosage (c) awareness of the limitations of BG monitoring technology. There is clearly an area where changes in education/support would benefit many. Abstract : We conducted an online survey of experience of BG monitoring in people with T2DM. Perceptions of shorter vs longer term consequences of hyperglycaemia varied widely. Only 9% recalled discussing BG metre accuracy when their latest metre was provided and 77% did not recall discussing BG metre performance with a healthcare professional ‐ this is clearly an area where changes in education and support would benefit many.